Sovereign Debt : A Survey of Some Theoretical and Policy Issues - Arora, Vivek (IMF Working Papers; Working Paper, 1993)
This paper surveys the literature on sovereign debt that deals with the issues of a country's ability-to-pay, its willingness-to-pay, and the policy responses to the debt crisis of the 1980s. The existence of an ability-to-pay problem suggests a need for debt reduction, but plans for debt relief face potential incentive problems, and sovereign debt repurchases are not always a welfare maximizing method of debt restructuring. The paper synthesizes the main conclusions on these issues. With a willingness-to-pay problem, the potential penalties for debt repudiation are important in the endogenous determination of the repayment outcome. Penalties that are intertemporal in nature have different implications for debt repudiation than do intratemporal penalties. In addition, the asymmetric distribution of the costs of default can lead to a recurrent cycle of debt accumulation and default.